Application of Classical Cryptography in Text Communication - Darsana, Wayan (Journal of Technology and Computer, 2024)
Advancements in data communications and computer networks have facilitated communication among numerous individuals using various hardware and software technologies. However, this progress also brings about a significant challenge: data and information security. Safeguarding data and information transmitted over communication networks necessitates the implementation of a data security system. One effective approach to achieve this is by utilizing cryptographic techniques. Cryptography involves encoding data transmitted through a network in a manner that only authorized parties can decipher. Data that remains unencrypted is referred to as plaintext, and once encrypted, it becomes ciphertext. Before the advent of computers, cryptography relied on character-based algorithms, often known as classical cryptographic algorithms. This research focuses on applying classical cryptography to encrypt and decrypt text data exchanged via chat applications. The test results demonstrate that the encryption and decryption processes effectively maintain data confidentiality.